Profile of upper extremity strength and function in division 1 collegiate athletes. (July 2020) - Pontillo, Marisa; Sennett, Brian J.
Abstract: Objectives: To profile shoulder strength and functional test scores in collegiate athletes across various sports. Design: Cross-sectional. Setting: Pre-participation physical screens for varsity athletes at a Division I university. Participants: 476 healthy Division 1 collegiate athletes (270 males; 27 varsity sports). Main outcome measures: Two trials of each 1. Isometric peak force (PF) using hand-held dynamometry for shoulder internal rotation (IR), external rotation (ER), and forward elevation (FE) in kg; 2. Closed Kinetic Chain Upper Extremity Stability Test (CKCUEST), quantified by number of touches. Results: PF values (mean(SD), dominant/non-dominant) for females were: IR = 8.7(2.6)/8.7(6.2); ER = 8.2(2.5)/7.9(2.5); FE = 8.0(2.5)/8.0(2.7); CKCUEST scores were 21.8(3.9). PF values for males were: IR = 12.0(3.8)/11.9(3.6); ER = 10.7(3.4)/10.7(3.5); FE = 10.7(3.5)/10.4 (3.5); CKCUEST scores were 26.0(4.1) touches. Conclusions: Normative values should be used as an athlete's baseline for the CKCUEST. This may help target athletes who are at a higher risk of upper extremity injury and help with goals or return to sport readiness during the rehabilitation process. Highlights: Baseline values of shoulder strength and functional testing has not been previously described thoroughly for athletes. In this study, shoulder strength testing and CKCUEST scores were profiled for healthy collegiate athletes across 27 different sports. Our reported shoulder strength and upper extremity functional test scores may be useful in determining baseline values for collegiate athletes. These values may identify at-risk athletes and aid in return to sport readiness during the rehabilitation process.